Problematika Guru Geografi Pada Sistem Sekolah Sehari Penuh - Nurhikmah, Nurhikmah; Umar, Ramli; Hasriyanti, Hasriyanti (LaGeografia, 2021)
Innovations in the world of education that continues to grow make all educators must adapt to the changes, one of which is the policy of Full day school. This study discusses 1) the implementation of teacher learning in the full-day school system 2) problems faced by teachers and 3) how solutions are done in addressing problems in the full-day school system at SMAN 4 Makassar. This type of research is descriptive qualitative. The data collection techniques use observation, interview, and documentation. The analysis methods used are three, namely data reducing, data presentation, conclusion and verification. The results of this study showed that the implementation of geography teacher learning in the full day school system at SMAN 4 Makassar which took place from morning to afternoon in the implementation of full day school learning many innovations that geography teachers do in the curriculum structure developed to support the learning of the full day school system. However, there are some problems experienced by geography teachers in the implementation of full day school system learning and finding solutions to the problems faced by geography teachers in SMAN 4 Makassar.